2020
DOI: 10.1038/s41598-020-60798-6
|View full text |Cite
|
Sign up to set email alerts
|

Parental non-hereditary teratogenic exposure factors on the occurrence of congenital heart disease in the offspring in the northeastern Sichuan, China

Abstract: nonhereditary factors play an important role in the occurrence of congenital heart disease (cHD). this study was to explore the possible parental nonhereditary exposure factors relevant to the occurrence of CHD in the northeastern Sichuan area. A total of 367 children with CHD and 367 children without congenital malformations aged 0 to 14 years old were recruited from the Affiliated Hospital of North Sichuan Medical College and Nanchong Central Hospital between March 2016 and November 2018. This study was desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Although we investigated detailed information on maternal pre-pregnancy infections, medication history, pre-pregnancy illnesses, and physiological and paternal behavioral habits during pregnancy, there are still some unmeasured factors (such as maternal diet and physical activities) or other seasonally varying factors that may bias the results. 42,43 In this multicenter study, we evaluated the association between maternal exposure to ECEs during the critical period of organ development and the development of fetal CHD in a Chinese population. Our study found that ECEs experienced by pregnant women during the embryonic period were associated with the development of fetal CHD and its various subtypes, especially PS, PA, and TOF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we investigated detailed information on maternal pre-pregnancy infections, medication history, pre-pregnancy illnesses, and physiological and paternal behavioral habits during pregnancy, there are still some unmeasured factors (such as maternal diet and physical activities) or other seasonally varying factors that may bias the results. 42,43 In this multicenter study, we evaluated the association between maternal exposure to ECEs during the critical period of organ development and the development of fetal CHD in a Chinese population. Our study found that ECEs experienced by pregnant women during the embryonic period were associated with the development of fetal CHD and its various subtypes, especially PS, PA, and TOF.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this study, the average daily temperature of the county was used to assess ECEs to minimize the impact of population mobility. Although we investigated detailed information on maternal pre-pregnancy infections, medication history, pre-pregnancy illnesses, and physiological and paternal behavioral habits during pregnancy, there are still some unmeasured factors (such as maternal diet and physical activities) or other seasonally varying factors that may bias the results. , …”
Section: Discussionmentioning
confidence: 99%
“…The results showed that tRF-58:74-Gly-GCC-1 was enriched for target genes in biological processes and adrenergic signaling in cardiomyocytes signaling pathways in cardiomyocytes. Currently, a large body of evidence suggests that CHD occurs as a result of the accumulation of environmental risk factors and an individual’s factors, and that exobiotic metabolic processes such as the elimination of environmental teratogens play an important role in the development and progression of CHD [ 48 , 52 , 53 ]. Therefore, tRF-58:74-Gly-GCC-1 may be involved in the biological processes leading to the development of CHD.…”
Section: Discussionmentioning
confidence: 99%
“…In Nanchong, there were two main sources of nitrate that pollute groundwater 32 . One was the discharge of sewage and waste water from the surface, such as sewage from urban septic tanks, sewage leaked from sewage pipes, or garbage piles leached by rainwater 11 . In the process of discharge, the polluted water from this source would seep into the river, thus polluting the groundwater resources 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, by using univariate and multivariate methods, we explored the possible parental nonhereditary exposure factors relevant to the occurrence of CHD in the northeastern Sichuan area and evaluated the relative importance of each risk factor 11 . However, we didn't develop an effective CHD prediction model built on comprehensive epidemiological data.…”
Section: Introductionmentioning
confidence: 99%